Utilization of Benime Application for Speaking Learning - Husna, Kuntum Haviza; Ine , Jelung; Rezi , Melisa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Here the researchers conducted a study using the Benime application, the Benime application is one of the media that can help educators to create interesting teaching materials and has many features that can be used. Benime application-based learning videos. In this study, the researcher used a qualitative research method, which requires data that is in accordance with the original, in which the researcher used an interview with one of the teachers at Madrasah Aliyah Negri 2 Koto Baru Padang Panjang, making observations by descending To that location. The benefit of this application is that it can help educators make a learning video, and also provide benefits to students in understanding a given material, and can have a positive impact on students by providing critical thinking about the material provided by educators. So that with the Benime application, it can facilitate the activities or activities of educators and students in learning speaking.